3D Modeling of Tumor Necrosis Factor Receptor and Tumor Necrosis Factor‐bound Receptor Systems. Issue 5 (11th January 2019) - Roy, Urmi
Abstract: The interactions between the tumor necrosis factor (TNF) and its receptor molecule are responsible for various signaling networks that are central to the functioning of human immune homeostasis. The present work is a computational study of certain structural aspects of this cell‐signaling protein, specifically focusing on the molecular level analyses of the TNF receptor (TNF‐R), guided by its crystallographic structure. We also examine the possible binding sites of the TNF onto TNF‐R, and the associated interactions. The structural and conformational variations in the TNF‐R and TNF bound TNF‐R systems are examined in this context using molecular dynamics (MD) simulations. The time dependent variations of the dimeric TNF‐R structures are compared with, and shown to be steadier than their isolated monomers. This dimeric stability is favored under acidic conditions. The results are used to further illustrate how 3D modeling and computer simulations can aid the structure‐based approach to probing a ligand‐receptor system. Abstract :